ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT PRODUK TEPUNG SERBA GUNA MEREK KOBE DI WILAYAH KABUPATEN KULON PROGO (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this study is to determine the effect of consumer attitudes on the attribute of the multipurpose flour kobe brand in Kulon Progo regency, by taking samples of 30 stores from 136 stores selling kobe brand versatile flour. This research uses data analysis method of fishbein and chi-squares, the result of the research method that is obtained is the attitude of consumer of all purpose flour kobe brand got confident attitude with score 4,1. Based on research method of writer, obtained by calculati on result of fishbein analysis known Ao weight score for product of its kind diverse and hygienic have highest confidence weight that is 0,2642, followed by cheap and affordable price also product have good taste get equal weight that is 0, 2459 and the last product attribute with price indicator according to taste quality get weight 0.2439. The overall value of consumer attitudes (Ao) for the kobe brand versatile flour attribute is 4.01, the value obtained in the fishbein model lies in the acceptance area of a confident attitude (5> Ao ≥ 4), from data that has been processed can be inferred attributes on the versatile flour of kobe brand in the form of price and product can be accepted with confidence by its consumers. Based on the research method of the authors obtained chi- squares test results obtained x2hitungsebesar 40.000 and x2 table N-1 or 301 = 29 then x table 42.56 because chi-squares x2h <x2t and Significant test of the table obtained 0,000 then 0,000 <0, 05 then it can be concluded Ho accepted and Ha rejected. Interpreted there is no difference in consumer attitudes toward price attributes based on turnover. Result of chi-squares test obtained χ2 count equal to 3,867 and x2 table = 42,56 with α = 0,276 because α> 0,05 show Ho accepted and Harejected can be interpreted there is no difference of consumer attitude toward product attribute based on turnover.